2014
DOI: 10.1016/j.nutres.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms are associated with dietary intake but not physical activity among overweight and obese women from disadvantaged neighborhoods

Abstract: Evidence suggests that depressive symptoms are associated with poorer dietary intake and inadequate physical activity; however, this association has not been examined in lower income overweight and obese African American women. The objective of this cross-sectional study was to examine the associations between depressive symptoms and diet and physical activity in 196 women (87% African American, ages 25–51). Higher depressive symptoms were hypothesized to predict poorer diet quality, greater emotional eating, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
73
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 59 publications
7
73
2
2
Order By: Relevance
“…In contrast to the previous findings, Whitaker, Sharpe, Wilcox, and Hutto (2014) found that symptoms of depression were positively associated ( p < .05) with dietary intakes of saturated fats as measured by 24-hr dietary recalls. In a study of 33 medication-free patients with depression, Sublette, Hibbeln, Galfalvy, Oquendo, and Mann (2006) found that low fatty acid levels were predictive of suicidal tendencies.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previous findings, Whitaker, Sharpe, Wilcox, and Hutto (2014) found that symptoms of depression were positively associated ( p < .05) with dietary intakes of saturated fats as measured by 24-hr dietary recalls. In a study of 33 medication-free patients with depression, Sublette, Hibbeln, Galfalvy, Oquendo, and Mann (2006) found that low fatty acid levels were predictive of suicidal tendencies.…”
contrasting
confidence: 99%
“…Previous studies have thus had mixed results when examining high PUFA (Hakkarainen et al, 2004; Nanri et al, 2014; Rogers et al, 2008; Stahl et al, 2014; Sublette et al, 2006) and saturated fatty acid (SFA) diets (Whitaker, Sharpe, Wilcox, & Hutto, 2014) and diets deficient in fatty acids for effects on mood and neurobehavioral conditions such as depression and anxiety. In addition, less work has been focused on the neuro-behavioral effects of consuming diets high in SFAs, despite the significant consumption of diets high in saturated fats in our society.…”
mentioning
confidence: 99%
“…However, relationships between diet and depression may be explained by 'reverse causality', wherein a change in dietary choices is prompted by depressive symptoms; diminished appetite is a symptom of major depression for many and there is also evidence to suggest that some with depression are more likely to consume high fat and sugar foods (Whitaker et al, 2014) and fewer fruits and Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jad vegetables (Payne et al, 2012). Although previous prospective studies have not found evidence to support the reverse causality hypothesis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…50 That is, a change in dietary choices could be prompted by depressive symptoms. Diminished appetite is a symptom of major depression for many and there is also evidence that some people with depression are more likely to consume high-fat and high-sugar foods 51 and fewer fruits and vegetables than their non-depressed counterparts. 52 However, an analysis of data from the Personality and Total Health (PATH) Through Life Study found that while current depression is associated with poorer dietary habits, a history of depression may prompt healthier dietary behaviors in the long term.…”
Section: Introductionmentioning
confidence: 99%